2021
DOI: 10.30650/jik.v9i2.3109
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Academic Procrastination among Students at Medicine Faculty Mulawarman University

Abstract: Academic procrastination is an act of intentionally postponing completion of assignments and can prevent individuals from starting of finishing assignments. This study aims to describe the prevalence of academic procrastination among students at Medicine Faculty, Mulawarman University. This is a descriptive observational study and the respondents were selected through purposive sampling technique. There were 216 students of 2018, 2019, and 2020 Academic Year at Medicine Faculty selected as the respondents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The findings are in line with the opinion that the factors that cause academic procrastination in students are internal factors and external factors including (Klassen et al, 2010), students do not understand the material presented by the teacher, are not confident in their abilities (Shaked & Altarac, 2022), are unable to manage time to do assignments and other activities, the four students feel bored and bored because of online/online learning, lack of attention and motivation to learn from parents, and what often happens is signal problems, cell phones, and internet quota (Balhara et al, 2022;Fentaw et al, 2022). In another study, it was explained that the factors that influence academic procrastination behavior are parenting style, environmental conditions, and family economic factors (Makbul et al, 2021;Putri Daryani & Yuni Nugrahayu, 2021).…”
Section: Research Resultsmentioning
confidence: 99%
“…The findings are in line with the opinion that the factors that cause academic procrastination in students are internal factors and external factors including (Klassen et al, 2010), students do not understand the material presented by the teacher, are not confident in their abilities (Shaked & Altarac, 2022), are unable to manage time to do assignments and other activities, the four students feel bored and bored because of online/online learning, lack of attention and motivation to learn from parents, and what often happens is signal problems, cell phones, and internet quota (Balhara et al, 2022;Fentaw et al, 2022). In another study, it was explained that the factors that influence academic procrastination behavior are parenting style, environmental conditions, and family economic factors (Makbul et al, 2021;Putri Daryani & Yuni Nugrahayu, 2021).…”
Section: Research Resultsmentioning
confidence: 99%
“…Therefore, students who are aware of what is expected of them, competent to do the work since it falls within their course of study, and making an effort to complete it but failing to do so are considered academic procrastinators (Putri et al, 2021). This particular form of procrastination is the most prevalent kind and is characterized by a persistent inclination to put off academic tasks.…”
Section: Time (Ozer Et Al 2019)mentioning
confidence: 99%
“…Moreover, studies such as that of Rockinson-Szapkiw et al [14] also revealed that textbook formats may affect students' study behaviors and habits, including academic procrastination [15][16][17]. Academic procrastination is a widespread problem among students and can greatly affect their academic achievements [18]. Numerous studies have cautioned against allowing such behavior to persist, as it may become ingrained in students' habits and negatively impact their psychological development [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%